Ginger extract (Zingiber officinale Roscoe) triggers apoptosis in hepatocarcinogenesis induced rats - Yasmin Anum MY; Shahriza ZA; Looi ML; Shafina Hanim MH; Harlianshah H; Noor Aini AH; Suzana M; Wan Zurinah WN (Penerbit UKM, 2008)
Ginger extract has been reported previously by our group to exhibit anticancer and an-tioxidant effects by reducing tumour burden and lipid peroxidation respectively in he-patocarcinogenesis induced rats. The current study examined the expression of pro-apoptotic protein caspase-8 and anti-apoptotic protein Bcl-2 in hepatocarcinogenesis treated rats. Thirty normal male Wistar rats were divided into 5 groups based on the diet given: i) control (normal rat chow), ii) olive oil, iii) ginger extract (100mg/kg body weight), iv) choline deficient diet + ethionine, CDE (to induce liver cancer) and v) CDE+ ginger extract. Rats were killed at week 8, and liver tissues were excised for immuno-histochemical study to identify pro-apoptotic and anti-apoptotic proteins, caspase-8 and Bcl-2. The observation on H&E staining confirmed the CDE diet induced liver can-cer as indicated by the presence of numerous oval cells. Identification of Bcl-2 expres-sion showed that 91.6% (11/12) of the samples from the CDE group revealed positive staining while treatment with ginger extract however inhibited the expression with only 8.4% (1/12) samples showing positive staining for Bcl-2. As for caspase-8 protein, 41.7% (5/12) of the samples from CDE group showed positive staining, which in-creased to 100% (12/12) with ginger extract treatment. Our findings suggest that gin-ger extract has an anticancer effect by inducing apoptosis in liver cancer cells via up-regulation of the expression of pro-apoptotic protein, caspase-8 and down-regulation of the expression of anti-apoptotic protein Bcl-2